Orbitofrontal Cortex and Thalamus Volumes in Patients with Delusional Disorder - Mermi, Osman; Keles, Denizhan; Kilic, M. Caglar; Baykara, Sema; Korkmaz, Sevda; Atmaca, Murad (Yerkure Tanitim & Yayincilik Hizmetleri A S, 2021)
Objective: We aimed to examine whether clinical similarity might also reflect to neuroanatomical regions of the brain, orbitofrontal cortex (OFC) and thalamus which seem to be important in the neuroanatomy of OCD and hypochondriasis. Methods: Volumes of OFC and thalamus were measured in eighteen patients and the same number of healthy control subjects. Manual tracing method was used when measured. Results: The mean left and right sides of volumes of the OFC were statistically significantly smaller than those of healthy control subjects whereas both sides of thalamus volumes were statistically significantly larger than those of healthy ones. When an General Linear Model, with the covariates of age, gender, and total brain volumes as covariates, was performed, we seen that statistical significance showing that the OFC volumes were reduced in patients with delusional disorder compared to those of healthy control subjects and that thalamus volumes were greater in the patient group than those of healthy comparisons were maintained. Conclusion: In conclusion, we found that patients with the delusional disorder had statistically significantly smaller volumes of the OFC and greater thalamus volumes compared to those of healthy control ones on both sides. As hypothesized by us, the clinical similarity was also reflected in neuroanatomical regions of the brain, OFC and thalamus which seem to be important in the neuroanatomy of OCD and hypochondriasis. However, our results require replication.
Keywords: OFC; Delusional Disorder; Thalamus; Volumes